Drying characteristics, kinetics model and effective moisture diffusivity of vacuum far-infrared dried Rehmanniae - Yunhong, Liu; Xiaofang, Li; Wenxue, Zhu; Lei, Luo; Xu, Duan; Yong, Yin (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Vacuum far-infrared radiation (VFIR) drying has recently received many attentions because of its effective and successful applications in drying some agricultural products. The VFIR drying of Radix Rehmanniae was conducted and Weibull distribution function was applied to fit the drying kinetics in this study. The results showed that the increase of radiation heater temperature and the decrease of chamber pressure could reduce drying time obviously. Compared with single diffusion equation, Weibull distribution function had higher precision to fit the drying curves of VFIR drying of Rehmanniae. The effective moisture diffusivity (Deff) increased with the increase of heater temperature and the decrease of pressure. Scanning electron telescope (SEM) analysis showed that more porous surface could be observed after VFIR drying, which is beneficial to enhance moisture diffusivity and drying rate as well. Keywords: vacuum far-infrared radiation drying, moisture ratio, effective moisture diffusivity, Rehmanniae, Weibull distribution function DOI: 10.3965/j.ijabe.20160905.2082 Citation: Liu Y H, Li X F, Zhu W X, Luo L, Duan X, Yin Y. Drying characteristics, kinetics model and effective moisture diffusivity of vacuum far-infrared dried Rehmanniae. Int J Agric & Biol Eng, 2016; 9(5): 208－217.